Persepsi Masyarakat Terhadap Pendidikan Agama Islam Di Sekolah Umum - Kuni Zakiyah; Davina Maulidia Chesta Adabi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to explore how society views Islamic religious education in public schools. Even though PAI has a significant contribution in building student character and ethics, there is still a negative stigma regarding it as an institution that is lagging behind and lacks professionalism. This study focuses on determining the factors that influence public perception and how the lack of information regarding the development of Islamic religious education contributes to this stigma. Research findings indicate that society’s understanding of PAI varies, with many parents preferring education at Islamic boarding schools compared to public schools, because they consider education at Islamic boarding schools to be more in-depth and comprehensive. On the other hand, negative perceptions often arise due to dissatisfaction with the curriculum which is considered traditional and does not meet the needs of modern society, such as teaching about muamalat and social ethics.